Circulating microparticles in patients with chronic hepatitis C and changes during direct-acting antiviral therapy - Husa, Petr; Snopková, Svatava; Zavřelová, Jiřina; Zlámal, Filip; Svačinka, Radek; Husa, Petr (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
BACKGROUND: Microparticles (MPs) are heterogeneous vesicles derived from membranes of different cells. Between 70 to 90% of MPs detected in blood originate from platelets. The release of MPs is associated with proinflammatory and procoagulant states. Elevated levels of MPs have been found in different diseases. We investigated MPs levels in patients with chronic hepatitis C (CHC) and changes in level during treatment using direct-acting antivirotics (DAA). PATIENTS AND METHODS: Thirty-six patients with CHC and forty healthy volunteers were included in the study. Concentrations of MPs were determined indirectly by measuring their procoagulant activity in plasma at baseline, end of therapy (EOT), and 12 weeks after EOT when the sustained virological response was assessed (SVR12). RESULTS: All patients achieved SVR12, which was associated with rapid improvement of markers of liver damage and function as well as liver stiffness (P=0.002). MPs levels were significantly higher in CHC patients than in healthy volunteers (P<0.001). No statistically significant decrease was found observed between baseline and SVR12 (P=0,330). Analysis of subpopulations with minimal fibrosis F0-1 (P=0.647), advanced fibrosis F2-4 (P=0.370), women(P=0.847), men (P=0.164) and genotype 1 (P=0.077) showed no significant changes during the follow-up period. CONCLUSIONS: MPs levels are higher in CHC patients and remain elevated shortly after achieving SVR. Higher concentrations of MPs in plasma are probably caused by a chronic uncontrolled exaggerated inflammatory response caused by CHC. Longer observation would probably confirm the significance of MPs levels decrease because normalization of liver function, inflammation, and structure after SVR requires more than 12 weeks.
Keywords: Fibrosis; Inflammation; Hepatitis C, Chronic; Humans; jaterní cirhóza; chronická hepatitida C; lidé; Antiviral Agents; fibróza; antivirové látky; Female; Male; zánět; Cell-Derived Microparticles; Sustained Virologic Response; setrvalá virologická odpověď; ženské pohlaví; mužské pohlaví; mikropartikule; Liver Cirrhosis